Forbidden Words and Female Anatomy. Gender and Language Taboos in the Oxford English Dictionary - Martina Guzzetti (Lea, 2023)
This paper focuses on English taboo vocabulary concerning female anatomy as represented in lexicography. It examines the Oxford English Dictionary and its many biases and subjectivity concerning gender, among other things. The analysis considers the three editions of the dictionary, the diachronic evolution of taboo words, how these have been defined in the OED, and tabooing practices like euphemism or dysphemism. Results show how linguistic censorship promotes the creation of highly inventive new expressions and sheds light on the culture(s) that enforce the use of taboo words and the ideologies behind their inevitably selective representation in lexicography.